Subgeneric classification of the genus Anthaxia Eschscholtz, 1829 (Coleoptera: Buprestidae: Anthaxiini) - Bílý, Svatopluk (Zootaxa, 2019)
The subgeneric classification of the genus Anthaxia Eschscholtz, 1829 is discussed and two new subgenera are created: Capanthaxia subgen. nov. and Richteraxia subgen. nov. A key to the subgenera of Anthaxia is presented as well as the characteristics of all subgenera with their main diagnostic characters. The subgenus Capanthaxia subgen. nov. is divided into three species-groups: Anthaxia (C.) aterrima Kerremans, 1903 species-group, A. (C.) capensis Kerremans, 1903 species-group and A. (C.) sulcicollis Obenberger, 1928 species-group. All principal diagnostic characters are illustrated.